2018
DOI: 10.1016/j.pss.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Aerosols: The key to understanding Titan's lower ionosphere

Abstract: The Permittivity Wave and Altimetry system on board the Huygens probe observed an ionospheric hidden layer at a much lower altitude than the main ionosphere during its descent through the atmosphere of Titan, the largest satellite of Saturn. Previous studies predicted a similar ionospheric layer.However, neither previous nor post-Huygens theoretical models have been able to reproduce the measurements of the electrical conductivity and charge densities reported by the Mutual Impedance (MI) and Relaxation Probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The actual supersaturation is not known, but is suggested by Irwin et al (2018) to be 0.13±0.12, which would require a charge of 50 electrons on a 7nm particle at the cloud base for nucleation. Charges of 30-50e on small aerosol particles have been predicted in the electron-rich atmospheres of Jupiter (Whitten et al, 2008) and Titan (Molina-Cuberos et al, 2018), and are well under the limit shown in figure 6(c). However, there are many uncertainties due to a lack of laboratory data on H2S and the difficulties of remotely sensing the troposphere.…”
Section: Neptune and Uranussupporting
confidence: 65%
“…The actual supersaturation is not known, but is suggested by Irwin et al (2018) to be 0.13±0.12, which would require a charge of 50 electrons on a 7nm particle at the cloud base for nucleation. Charges of 30-50e on small aerosol particles have been predicted in the electron-rich atmospheres of Jupiter (Whitten et al, 2008) and Titan (Molina-Cuberos et al, 2018), and are well under the limit shown in figure 6(c). However, there are many uncertainties due to a lack of laboratory data on H2S and the difficulties of remotely sensing the troposphere.…”
Section: Neptune and Uranussupporting
confidence: 65%
“…Curtius et al (2006) showed that ions act as nucleation cores for the attachment of the supersaturated gas phase molecules. Such mechanisms have been shown to be efficient on Titan (Imanaka et al 2004;Gronoff et al 2009a,b) where cosmic rays trigger aerosols (Lavvas et al 2012) that are 'the key to understanding Titan's lower ionosphere' (Molina-Cuberos et al 2018). Although Titan's atmospheric chemistry is different to that of Mars, the fact that the observed Mars detached layer occurs west of the magnetic anomaly suggests that these mechanisms could also be at work.…”
Section: Discussionmentioning
confidence: 99%
“…Dept. Electromagnetism and Electronic, University of Murcia, Murcia, Spain (gregomc@um.es) 2 European Space Agency, ESA/ESTEC, Directorate of Science, Noordwijk, Netherlands (owitasse@cosmos.esa.int) 3 Laboratoire Atmosphères, Milieux, Observations Spatiales, Guyancourt, France (franck.montmessin@latmos.ipsl.fr) 4 Laboratoire Atmosphères, Milieux, Observations Spatiales, Guyancourt, France (jean-jacques.berthelier@latmos.ipsl.fr)…”
mentioning
confidence: 99%
“…A model was developed based on studies performed at Mars and Titan [1][2], which computes the atmospheric positive and negative electrical conductivities between 0.1 and 15 bars in the atmosphere of Neptune and Uranus. In this altitude range, galactic cosmic rays ionize the atmospheric constituents, which react with atmospheric neutrals and aerosols, leading to the formation of ions heavier than the ones produced by cosmic rays.…”
mentioning
confidence: 99%